Rancang Bangun Kombinasi Trafo 1 Ampere CT dan 5 Ampere Engkel Untuk Efisiensi Power Amplifier Class GB (Groudbridge) - Arief Budi Laksono (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2019)
Along with the development of technology about audio soundsystems, innovations and new designs about audio are very many, music is an entertainment that is almost every day encountered by people today, Amplifier products that are commonly marketed (finished products) are still very dominated by the outside market country. GB Power Amplifier class (Ground Bridge) is one type of power amplifier that requires a high input voltage in the audio world, the use of a combination of suitable transformers and with the output voltage transformer that is able to meet the required power capacity for the amplifier without having to search for transformer with a high output specification. So a good component selection can make the power amplifier's performance to the maximum.